Supplemental fisheries life history data for selected lakes and streams in the AOSERP Study Area ... - Herbert, B. K. (University of Alberta Library, 1979)
During 1977, various rivers and lakes from the MacKay, Richardson, and Maybelle river drainages, the Ells River headwaters, and the east slope of the Birch Mountains were spot sampled for fish. Life history information and location data for the 672 fish, of 17 species, collected from these areas are presented in table format. The 17 species collected during this. survey are as follows: Arctic Grayling, Lake Whitefish, Lake Cisco, Lake Trout, Northern Pike, Longnose Dace, Lake Chub, Pearl Dace, Longnose Sucker, White Sucker, Burbot, Trout-Perch, Brook Stickleback, Ninespine Stickleback, Yellow Perch, Walleye, and Slimy Sculpin. ...